Antimicrobial activity of Ethyl Acetate Extracts of D. hamiltonii on Microbial Isolates of Spoiled Vegetables and Pathogenic Microorganisms - VIMALA, Y.; SUMATHI DEVI, K.; ELIZABETH, K.M. (Asian Journal of Chemistry, 2010)
The antimicrobial activity of Decalepis hamiltonii was tested by disc diffusion method against microbial isolates from spoiled vegetables and pathogenic microorganisms. The crude aqueous extract, cold ethyl acetate extract, ethyl acetate distillate and residual extracts of the roots were used for the study. The crude extracts showed largest zones to LF1 (isolate), AG (isolate), B (isolate), Pseudomonas aeruginosa, i.e., 8 mm zones. The cold ethyl acetate extract showed maximum activity against LF2 (isolate), i.e., 24 mm. The distillate showed activity against P2 (isolate) and B (isolate), i.e., 15 mm. The residual extract showed maximum activity against Aspergillus flavus (27.5 mID), Salmonella typhimurium (27.5 mm), AG (isolate) (25.0 mID), LF3 (isolate) (25.0 mm) indicating that the residual extracts were strongly inhibitory. The results indicate that the residual extracts can be used as broad spectrum antimicrobial agent.